2011
DOI: 10.1016/j.eswa.2011.04.092
|View full text |Cite
|
Sign up to set email alerts
|

The mixed capacitated general routing problem with turn penalties

Abstract: suggested. The experimental results show that the average deviation of the suggested solution method is less than 0.05 per cent with respect to optimum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…This set has been recently used by Bräysy et al (2011) as a benchmark set to test the efficiency of a memetic algorithm for a capacitated vehicle routing problem.…”
Section: Other Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This set has been recently used by Bräysy et al (2011) as a benchmark set to test the efficiency of a memetic algorithm for a capacitated vehicle routing problem.…”
Section: Other Resultsmentioning
confidence: 99%
“…It is worth commenting here that the idea of solving a single-vehicle routing problem by transforming it into an ATSP through an AGTSP has been recently generalized to solve different hard multivehicle routing problems, as we can see through the papers by Soler et al (2009), Baldacci et al (2010, Bräysy et al (2011), and Micó and Soler (2011).…”
Section: Given a Directed Graph G = (V A) With Nonnegative Costs Assmentioning
confidence: 99%
“…Downloaded 12/15/14 to 132.236.27.111. Redistribution subject to SIAM license or copyright; see http://www.siam.org/journals/ojsa.php Some tools support detailed street routing constraints, like U-turns, turning penalties (Bräysy et al [6]), street side management (e.g., meandering/zigzagging) (Irnich [38]), dynamic usability of roads (e.g., due to congestion or accidents), and hazmat (hazardous material) routing constraining the feasible path options (Akgün et al [1]). …”
Section: Plan Related Constraintsmentioning
confidence: 99%
“…Bautista and Pereira showed that when the restricted turns are numerous, they should be considered during the construction phase. Later, Soler et al and Bräysy et al studied the mixed general routing problem with turn penalties. Lacomme et al adapted Dijkstra's algorithm to compute the shortest paths between all pairs of edges.…”
Section: Related Workmentioning
confidence: 99%
“…Specifically, for a given priority class p that is not the lowest, the total number of times a vehicle enters a link at class p or higher must be greater than or equal to the number of times it leaves for the same class. The flow conservation constraints (6) ensure that each vehicle entering link j is coming from an adjacent link i and leaving through another adjacent link m. Constraints (7) ensure that all the required links are serviced during the corresponding priority class. Constraints (8) and (9) ensure that each vehicle starts at the depot and exits the network when its route is completed.…”
Section: Mathematical Formulationmentioning
confidence: 99%